Fungicidal Activity of the Root Extracts of Vitis vinifera - Tripathi, Durga (Asian Journal of Chemistry, 2010)
Anitmicrobial activity of some plant extracts have been found to inhibit or accelerate the growth of microbes and control of various types of diseases caused by fungi and bacteria. With this view, the present investigations have been carried out to determine the antifungal activity of successive extracts of roots of Vitis vinifera against some highly human and animal pathogenic fungi.